Pre-service teacher identity crisis regarding the educational changes generated by remote teaching due to the 2020 pandemic (2021)
The purpose of this research is to characterize the pedagogical factors that generated a teacher identity crisis pre-service teacher due to the change to remote teaching during the pandemic. Since the educational system has undergone significant changes as a result of the pandemic, in both the curriculum and the physical structure, teachers must adjust the way they teach now that they are facing important factors that influence their pedagogical and methodological decisions. This qualitative study conformed to the interpretative approach; data collection entailed an interview to 4 pre-service teachers of the English teaching program at Universidad Católica Luis Amigó, in Medellín. Researchers confirmed that new challenges arose in regard to both school dynamics and classroom management; although the education system implemented remote teaching as a temporary solution, teachers had to drastically adapt their lessons and methodologies. Pre-service teachers experienced difficulties regarding their teacher identity and the management of groups and parents under this new modality.